MiR529a controls plant height, tiller number, panicle architecture and grain size by regulating SPL target genes in rice (Oryza sativa L.). (January 2021) - Yan, Yan; Wei, Mingxiao; Li, Yu; Tao, Hua; Wu, Haoyu; Chen, Zhufeng; Li, Can; Xu, Jian-Hong
Highlights: OsSPL2, OsSPL17 and OsSPL18 at seedling stage were regulated by miR529a, but with complicated mechanism to control plant height. OsSPL2, OsSPL16, OsSPL17 and SPL18 control plant height and tiller number at tillering stage. MiR529a regulates panicle architecture and grain size through altering the expression of OsSPL2, OsSPL7, OsSPL14, OsSPL16, OsSPL17 and OsSPL18 . Abstract: Rice is one of the most important food crops in the world. Breeding high-yield, multi-resistant and high-quality varieties has always been the goal of rice breeding. Rice tiller, panicle architecture and grain size are the constituent factors of yield, which are regulated by both genetic and environmental factors, including miRNAs, transcription factors, and downstream target genes. Previous studies have shown that SPL (SQUAMOSA PROMOTER BINDING-LIKE) transcription factors can control rice tiller, panicle architecture and grain size, which were regulated by miR156, miR529 and miR535. In this study, we obtained miR529a target mimicry (miR529a-MIMIC) transgenic plants to investigate plant phenotypes, physiological and molecular characteristics together with miR529a overexpression (miR529a-OE) and wild type (WT) to explore the function of miR529a and its SPL target genes in rice. We found that OsSPL2, OsSPL17 and OsSPL18 at seedling stage were regulated by miR529a, but there had complicated mechanism to control plant height. OsSPL2, OsSPL16, OsSPL17 and SPL18 at tillering stage were regulated by miR529a to control plant height and tiller number. And panicle architecture and grain size were controlled by miR529a through altering the expression of all five target genes OsSPL2, OsSPL7, OsSPL14, OsSPL16, OsSPL17 and OsSPL18 . Our study suggested that miR529a might control rice growth and development by regulating different SPL target genes at different stages, which could provide a new method to improve rice yield by regulating miR529a and its SPL target genes.